2015
DOI: 10.1016/j.bej.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel respirometric methodology to characterize mass transfer and activity of H2S-oxidizing biofilms in biotrickling filter beds

Abstract: Application of a novel respirometric methodology to characterize mass transfer and activity of H2S-oxidizing biofilms in biotrickling filter beds, Biochemical Engineering Journal http://dx.doi.org/10.1016/j.bej. 2015.02.030 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
10
0
6
Order By: Relevance
“…A better performance was achieved in the present work by the BTF in co‐current flow using Pall rings, a packing material with low specific surface area. Such result is consistent with previous work reporting that the specific surface area of the packing material is not a critical design parameter in biogas desulfurization . Such high H 2 S ECs have not been reported in neutrophilic desulfurization, which suggests an improvement related with the co‐current operation.…”
Section: Resultsmentioning
confidence: 66%
“…A better performance was achieved in the present work by the BTF in co‐current flow using Pall rings, a packing material with low specific surface area. Such result is consistent with previous work reporting that the specific surface area of the packing material is not a critical design parameter in biogas desulfurization . Such high H 2 S ECs have not been reported in neutrophilic desulfurization, which suggests an improvement related with the co‐current operation.…”
Section: Resultsmentioning
confidence: 66%
“…Jiang et al showed through simulations that the HS − was oxidized in the biofilm, generating profiles that could allow the co‐existence of sulfide‐oxidizing and heterotrophic biomass. Bonilla‐Blancas et al also indicated that under high oxygen concentration conditions, the sulfide can be completely degraded in the biofilm. Thus, the mass transfer resistance and chemical/biochemical reaction inside the biofilm also could explain the better performance of the system with zeolite.…”
Section: Resultsmentioning
confidence: 98%
“… 47 ). Afterwards, the stoichiometric and kinetic parameters were estimated using the least square method, which minimizes the quadratic error between predicted and measured profiles of the substrates, storage products, and OUR profiles 48 . A version of AQUASIM 2.0 was used to determine the parameter surfaces 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Energy demands to operate the sludge anaerobic digester included the requirements for heating. The amount of heat (kWh) required per 1000 kg of wet sludge was calculated from the difference between the assumed initial (20 °C) and desired (35 °C) temperatures, multiplied by the specific heat capacity of sludge with 6% solids (4.18 kJ/kg °C) 48 , and the heat loss from the AD system with available heat transfer coefficients 52 . The energy requirement for stirring in the AD system was excluded because it required much less than that for the heating of sludge or heat loss from the AD system 53 .…”
Section: Methodsmentioning
confidence: 99%